PENYUSUNAN PEMBUKUAN DAN LAPORAN KEUANGAN UNTUK USAHA MIKRO DAN KECIL DI WILAYAH KAMPUNG PULO GEULIS BOGOR - Suhartati, Titi (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2020)
Micro and small businesses are growing rapidly in the community but have weaknesses in the process of recording, accounting and compiling financial reports in accordance with applicable standards. The purpose of this activity is to provide training and mentoring on bookkeeping and compilation of simple financial reports to the micro and small business in the Kampung Pulo Geulis area, Babakan Pasar, Bogor as the activity partner. Community service activities seek to improve the ability of micro and small business managers and expected to improve the economic quality of the community in the area which has processed of developing into a tourism area in Central Bogor. The method of implementing activities are training and assisting of the activity of the participants which can provide optimal results to improve the community's economy, especially for those who need additional funds for their business. The selected samples are 25 micro and small businesses as the participants. The training was in the form of lectures and practicums accompanied by consulting and assisting in preparing a simple of financial report. The results of this activity will be in the form of simple bookkeeping guidelines and preparation of financial statements for micro and small businesses that can be understood by the participants.